(untitled) (Global Scientific Review, 2023)
The article presents studies of the effectiveness of a new anti-cough drug "Bronchotus forte" by the method of determining the level of cytokines in the blood. White male rats in which acute inflammation was reproduced were used for the experiment. The amount of cytokines IL -1β, IL-6 and TNFα was determined in the blood of healthy and experimental rats by enzyme immunoassay. As a result of the studies it was revealed that the investigated preparation "Bronchotus forte - eleksir" reduced the severity of the inflammatory process caused by carageenin and provided an adaptive response in inflammation, and surpassed the effect of the branded comparison preparation "Codelac® Broncho with thyme - eleksir", produced by "Pharmstandart - Leksredstva" OJSC, Russia